Edukasi Perilaku Hidup Bersih dan Sehat pada Siswa Sekolah Menengah Pertama - Ngongo, Arniati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2026)
Clean and Healthy Living Behavior (PHBS) is a strategic effort to improve public health, especially among school-aged children. Low understanding and implementation of PHBS, such as handwashing and maintaining dental and oral hygiene, remains a problem among junior high school students. Therefore, this community service activity aims to increase students' knowledge and awareness of the importance of implementing PHBS in their daily lives. The activity was carried out at SMP Negeri Satap 1 Riung, targeting 95 students through interactive health education. The community service methods included lectures, discussions, the use of posters and leaflets, demonstrations, and direct practice of proper handwashing. This activity is expected to be the first step in establishing sustainable, clean and healthy living behaviors in the school environment.